Orchestrating Strategic Innovation for Educational Institution Resilience: A Dynamic Capabilities-Based Framework - Jemmy Jemmy; Selamet Riyadi; Setyani Dwi Lestari; Dina Nadiyah Faiqoh; Dadet Sugiarto (Oikonomia : Journal of Management Economics and Accounting, 2025)
Contemporary educational institutions face unprecedented challenges in an increasingly volatile, uncertain, complex, and ambiguous (VUCA) environment, with approximately 244 million children globally remaining out of school and significant digital divides exacerbated by the COVID-19 pandemic. This study addresses the critical research gap regarding how strategic innovation orchestration through dynamic capabilities builds institutional resilience in educational settings. The research employs an integrative literature review methodology, systematically analyzing 127 peer-reviewed studies from 2004-2024 across multiple databases including Scopus, Web of Science, ERIC, and ProQuest Education. The methodology combines deductive and inductive thematic analysis to synthesize diverse theoretical perspectives from strategic management, organizational behavior, and educational administration. The findings reveal that strategic innovation manifests through three interconnected dimensions: pedagogical innovation (74.0% prevalence), technological innovation (68.5%), and organizational innovation (59.8%). Dynamic capabilities—sensing (70.1%), seizing (64.6%), and reconfiguring (61.4%)—serve as critical mediating mechanisms between strategic innovation and institutional resilience, which operates through anticipation (71.7%), coping (77.2%), and adaptation (66.9%) processes. The study demonstrates that institutional resilience emerges from coherent orchestration of multiple innovation dimensions rather than isolated interventions, with correlation coefficients ranging from 0.68 to 0.76 across capability-resilience dimensions. The proposed integrative framework contributes to dynamic capabilities theory and organizational resilience literature while providing educational leaders with actionable guidance for strategic decision-making and systematic capability development in building institutional resilience for uncertain futures.